2022
DOI: 10.1136/bmjopen-2022-063524
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in chronic haemodialysis (MAGIC-HD): a study protocol for a randomised controlled trial to determine feasibility and safety of using increased dialysate magnesium concentrations to increase plasma magnesium concentrations in people treated with haemodialysis

Abstract: IntroductionPeople treated with haemodialysis are at increased risk for all-cause and cardiovascular mortality. Plasma magnesium concentration has been inversely associated with these risks. Therefore, plasma magnesium may be a new modifiable risk factor and an increase of dialysate magnesium concentration may be an easy, safe and effective way to increase plasma magnesium concentrations. Detailed information on modulating dialysate magnesium concentrations is limited in literature. Primary objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A recent Japanese, two-year observational study in hemodialysis patients demonstrated an inverse association for Mg concentration and the risk of hip fractures, with an OR 0.96 [0.94–0.99] per 0.1 mmol/L increase of plasma Mg [ 104 ]. Although, theoretically, an extreme increase of dialysate Mg is imaginable, only cautious dialysate increases are investigated due to the risk of fast intra- and extracellular electrolyte shifts during as well as between dialysis sessions [ 44 , 46 , 99 , 105 ]. Symptomatic hypermagnesemia, generally only seen in people with serum Mg concentrations of 1.6 to 2.0 mmol/L or above, is very rare, usually iatrogenic, and can follow decreased renal excretion, intra- to extracellular compartment shifts, and most frequently from excessive intake [ 106 ].…”
Section: Risks Of Magnesium Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Japanese, two-year observational study in hemodialysis patients demonstrated an inverse association for Mg concentration and the risk of hip fractures, with an OR 0.96 [0.94–0.99] per 0.1 mmol/L increase of plasma Mg [ 104 ]. Although, theoretically, an extreme increase of dialysate Mg is imaginable, only cautious dialysate increases are investigated due to the risk of fast intra- and extracellular electrolyte shifts during as well as between dialysis sessions [ 44 , 46 , 99 , 105 ]. Symptomatic hypermagnesemia, generally only seen in people with serum Mg concentrations of 1.6 to 2.0 mmol/L or above, is very rare, usually iatrogenic, and can follow decreased renal excretion, intra- to extracellular compartment shifts, and most frequently from excessive intake [ 106 ].…”
Section: Risks Of Magnesium Administrationmentioning
confidence: 99%
“…Additionally, results of RCTs investigating the effect of increasing dialysate Mg concentration are expected. The MAGIC-HD study, is a randomized, placebo-controlled feasibility study in a hemodialysis population, with a stepwise increase of dialysate Mg from the regular 0.50 mmol/L up to 1.00 mmol/L and explorative endpoints including PWV, 48 h cardiac rhythm registrations, and several markers of vascular calcification and MBD [ 105 ]. Another large, cluster randomized clinical trial will investigate cardiovascular-related hospitalization, mortality, and patient-reported muscle cramps comparing higher (0.75 mmol/L) versus lower (0.50 mmol/L) hemodialysate Mg concentration (ClinicalTrials identifier: NCT04079582).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Decreasing Mg changes was significantly associated with high Mg dialysate concentration. In line with this, the ongoing Magnesium in chronic haemodialysis (MAGIC-HD) study, a randomized double-blinded standard of care-controlled trial will evaluate the feasibility of sequential Mg increase (from 0.5 to 1 mmol/L) in the dialysate [43].…”
Section: Dialytic Balance Of Calcium and Magnesium During The Sessionmentioning
confidence: 99%
“…The development of hypomagnesemia in patients with CKD and ESKD may be attributed to the use of certain drugs, including diuretics, calcineurin inhibitors, proton pump inhibitors, and epidermal growth factor inhibitors [29]. Recently, a published protocol outlines a randomized, double-blinded, care-controlled trial aimed at determining the safety and feasibility of gradually increasing magnesium concentrations in hemodialysis-treated patients [30]. However, to comprehensively investigate the effects of magnesium levels in CKD patients and assess its potential as a therapeutic tool for regulating hyperuricemia, further studies, including randomized controlled trials, are warranted.…”
mentioning
confidence: 99%